2006
DOI: 10.1159/000092348
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Iron Deficiency Anemia with Intravenous Iron Preparations

Abstract: Objective: We aimed to determine the effects of intravenous iron therapy on blood parameters in pediatric patients who do not tolerate oral iron therapy for any reason. Patients and Methods: The patient group consisted of candidates for elective operations requiring blood transfusions in order to raise hemoglobin (Hb) concentrations rapidly and for whom oral iron administration is useless and compliance with long-term treatment is definitely impossible due to sociocultural factors. Sixty-two children were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…[22] The experience with iron sucrose administration for children with IDA is very limited. Akarsu et al [7] evaluated its efficacy and safety in 62 children with IDA. The pretreatment level of hemoglobin rose from 7.9±1.2 g/dL to 11.4±1.1 g/dL three months after therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] The experience with iron sucrose administration for children with IDA is very limited. Akarsu et al [7] evaluated its efficacy and safety in 62 children with IDA. The pretreatment level of hemoglobin rose from 7.9±1.2 g/dL to 11.4±1.1 g/dL three months after therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The experience with IV iron sucrose for the treatment of IDA in children is very limited, and all manufacturers do not recommend its use in children due to lack of adequate pediatric data. [7][8][9] We describe herein our department's experience with the use of IV iron sucrose in children with IDA that were intolerant, non-compliant or failed to respond to oral iron therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The study in 18-to 180-month-old children who were scheduled for elective surgery showed significant improvements in Hb from month 1 to the end of the 3-month study period [78]. Children in the control group who were treated with oral ferrous glycine sulfate (no details on dosing reported) achieved a similar Hb increase.…”
Section: Pediatric Populationsmentioning
confidence: 85%
“…Two studies were performed in iron-deficient children and adolescents with low Hb levels [78,79] and treated with IS at individual doses of 6.5 --18.1 mg iron/kg and 5 mg/kg, respectively. The study in 18-to 180-month-old children who were scheduled for elective surgery showed significant improvements in Hb from month 1 to the end of the 3-month study period [78].…”
Section: Pediatric Populationsmentioning
confidence: 99%
See 1 more Smart Citation